156k views
4 votes
Quick help and you'll get a solid 15

Quick help and you'll get a solid 15-example-1
User Aerion
by
4.9k points

2 Answers

3 votes

Answer:

A

Explanation:


$ \frac {{(a)/(b)+1}}{{(b)/(a) - 1}} = \frac{{(a)/(b) + (b)/(b)}}{{(b)/(a) - (a)/(a)}} = \frac{{\frac{{a + b}}{b}}}{{\frac{{b - a}}{a}}} = \frac{{a + b}}{b}*\frac{a}{{b-a}}=\frac{{a(a+b)}}{{b(b-a)}}

User David Andreoletti
by
5.4k points
6 votes
i believe it’s b or d i’m sorry if i get it wrong
User Rory Lester
by
5.1k points